2019
DOI: 10.4102/ojvr.v86i1.1734
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and restriction fragment length polymorphism analysis of canine parvovirus 2 (CPV-2) in dogs in southeast Anatolia, Turkey

Abstract: Canine parvovirus-2 (CPV-2) is the aetiological agent of an infectious viral disease of dogs, characterised by diarrhoea and vomiting. Mutations of the CPV-2 genome have generated new variants circulating worldwide. This article reports the molecular analysis of CPV-2 variants collected in the dog population in southeast Anatolia, Turkey. Twenty blood samples previously taken for the laboratory diagnosis of dogs with suspected parvovirus were screened for CPV-2 by polymerase chain reaction (PCR). Of the 20 sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 42 publications
0
9
0
1
Order By: Relevance
“…In Turkey, its epidemiological presence has been revealed by serological tests such as ELISA (Saltık and Kale 2020) and neutralization tests (Gencay et al 2004). When we look at the recent studies, even though there are many studies in our country for diagnosing respiratory and digestion system infections (Avci et al 2016, Dinçer 2017, Polat et al 2019, Timurkan et al 2021), those about CDV are quite limited (Oğuzoğlu et al 2018). During these limited amounts of studies, CDV genome presence has been revealed by RT-PCR method.…”
Section: Resultsmentioning
confidence: 99%
“…In Turkey, its epidemiological presence has been revealed by serological tests such as ELISA (Saltık and Kale 2020) and neutralization tests (Gencay et al 2004). When we look at the recent studies, even though there are many studies in our country for diagnosing respiratory and digestion system infections (Avci et al 2016, Dinçer 2017, Polat et al 2019, Timurkan et al 2021), those about CDV are quite limited (Oğuzoğlu et al 2018). During these limited amounts of studies, CDV genome presence has been revealed by RT-PCR method.…”
Section: Resultsmentioning
confidence: 99%
“…The importance of emerging (SARS/MERS) and re-emerging (CPV-2c or COVID-19) infections is currently increasing [2,23,24]. Therefore, the genetic characteristics of these infectious agents need to be examined frequently due to emerging new types, changes in pathogenesis, and the dynamism of immune escape mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Розвиток науки сприяє удосконаленню засобів діагностики та профілактики інфекційних захворювань взагалі та вірусних хвороб собак зокрема. З цією метою широко використовують молекулярно-генетичні методи (Csagola, Varga, Lorincz, & Tuboly, 2014;Hao et al, 2019;Matsuda, 2017;Zhou, Zeng, Zhang, & Li, 2017 (Miranda, & Thompson, 2016;Polat, Sahan, Aksoy, Timurkan, & Dincer, 2019;Sun et al, 2019;Tucciarone et al, 2018) В Україні вакцинація парвовірусного ентериту собак -один із головних заходів боротьби із захворюванням.…”
Section: вступunclassified